An empirical study of consumers' perceptions towards Financial Advisory Services. - Chong, Siat Yin. (2008)
This study seek to determine the expectations of the local working population in their initial selection process of financial advisory representatives (FARs). In addition, we want to assist different types of institutions gain a better understanding of what consumers look for in the initial selection of financial advisory services.